Skin Barrier Dysfunction in Endurance Athletes: A Narrative Review of Mechanisms, Environmental Stressors, and Clinical Implications - Kaliciak, Iwona; Korda, Oliwia (Quality in Sport, 2026)
The skin of the endurance athlete functions as a load-bearing, evaporative, antimicrobial, and photoprotective interface that is repeatedly stressed during prolonged training and competition. This narrative review examines how endurance-training exposures disturb the skin barrier and translate into clinical skin disease in runners, ultramarathoners, triathletes, and cyclists. PubMed, PubMed Central, and publisher sources were searched for athlete-specific and mechanistic skin-barrier literature, with priority given to work published from 2016 onward and evidence organised by mechanism and exposure rather than by diagnosis. Prolonged, repetitive mechanical loading, sweat and hyperhydration, occlusion by clothing and equipment, ultraviolet radiation, and thermal and water exposure, together with transient post-exercise shifts in surface pH, lipids, antimicrobial peptides, and microbial ecology, generate a recurrent pattern of friction blisters, chafing, intertrigo, folliculitis, saddle sores, tinea, irritant and contact dermatitis, xerosis, sunburn, and cumulative photodamage rather than a single uniform disorder. Effective prevention is mechanism-based, combining sport-specific friction control, rapid removal of wet garments, gentle cleansing, barrier-supportive moisturisation, early recognition of infection, and redundant photoprotection. Prospective studies linking objective barrier biomarkers to clinical outcomes are needed to individualise prevention.